2022
DOI: 10.1111/1365-2435.13994
|View full text |Cite
|
Sign up to set email alerts
|

The effect of niche filtering on plant species abundance in temperate grassland communities

Abstract: 1. Niche filtering predicts that abundant species in communities have similar traits that are suitable for the environment. However, niche filtering can operate on distinct axes of trait variation in response to different ecological conditions.Here, we use a trait-based approach to infer niche filtering processes and (a) test if abundant and rare species in grassland communities are differently positioned along distinct axes of trait variation, (b) determine if these trait variation axes, as well as phylogenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 89 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…Lepš (2004b) showed that Molinia caerulea alone was more stable than total community biomass. Similarly, Arnillas et al (2021) andPadullés Cubino et al (2022) showed that dominant versus nondominant species possessed different traits and their life strategies can strongly differ. Besides this biological effect, the higher stability of abundant species is also connected with a pure statistical effect where a high biomass is usually connected with increased number of independent units (ramets) resulting in the averaging of their…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lepš (2004b) showed that Molinia caerulea alone was more stable than total community biomass. Similarly, Arnillas et al (2021) andPadullés Cubino et al (2022) showed that dominant versus nondominant species possessed different traits and their life strategies can strongly differ. Besides this biological effect, the higher stability of abundant species is also connected with a pure statistical effect where a high biomass is usually connected with increased number of independent units (ramets) resulting in the averaging of their…”
Section: Discussionmentioning
confidence: 99%
“…Via the dominance effect, diversity can be destabilizing at the population level (Gross et al, 2014), however, at the community level, the opposite pattern can be observed as other mechanisms can prevail. Higher stability in populations of more stable species is likely linked to their characteristics (Arnillas et al, 2021;Májeková et al, 2014) and, at the same time, these traits can be also responsible for higher abundance of those species (Lisner et al, 2021;Padullés Cubino et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Abrupt decreases in plant productivity during drought are likely to already occur under mild drought intensities for fast‐strategy plant communities as they prioritize growth over durability (Oliveira et al, 2021). Fast‐strategy plants are also generally established in environments that are less water and nutrient limited compared to their slow‐strategy counterparts (Padullés Cubino et al, 2022; Pérez‐Ramos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…, whose resulting spatial distribution patterns might be overridden by other ecological processes that act during the lifetime of individual trees(Levine & Murrell 2003). On the other hand, fruit and seed traits may show a long-lasting effect on the abundance of large trees, as shown for grass species(Padullés et al 2022). The larger seeds of M. racemosa might promote higher survival and establishment of young seedlings (Moles & Westoby 96 2004), and allow the observed highest species abundance in seasonally flooded patches in comparison to the other two Myrcia species.…”
mentioning
confidence: 99%